THE RADIATION CREATION OF V-CENTERS IN KCl, KBr AND KI CRYSTALS IN THE FIELDS OF LIGHT CATIONS, PLASTIC AND ELASTIC STRESS - Bizhanova, K.; Shunkeyev, K. (Recent Contributions to Physics, 2018)
Using the absorption spectroscopy method the work researches the efficiency of X-ray created V-centers in KCl, KBr and KI crystals in the fields light cations, plastic and elastic stress. It is established that the interaction of two interstitial halogen atoms in the field of light cation favors the efficiency of V4A º (X3-)aca0MA+Xi- - centers and in the field of divacancies - (va+ vc-) - V2 º(X3-)aca0-centers. In the field of elastic stress the V-center creation efficiency in KCl crystal does no change, in KBr crystal – slightly decreases at the expense of increase of Br2– center creation efficiency, in KI crystal - sharply decreases. The effect of the radiation defect creation decrease in KI crystal in the field of elastic tension is explained with the energy unfavourableness of the self-trapped exciton decay into initial radiation defects – F, H –pairs.